Lower urinary tract symptoms in men: A case-based discussion - Bailly, Greg; Nickel, J. Curtis (Canadian Urological Association Journal, 2012)
At the conclusion of the sessions on lower urinary tract symptoms (LUTS) in men, participants at the 2012 Canadian Urology Forum (academic and clinical urologists from across Canada) engaged in a discussion of optimal LUTS evaluation and management. The discussion was led by Dr. J. Curtis Nickel and was based on a patient case. This review provides a summary of the case and the discussion it generated.